2016
DOI: 10.1186/s13584-016-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

Views of health system policymakers on the role of research in health policymaking in Israel

Abstract: BackgroundThe use of research evidence in health policymaking is an international challenge. Health systems, including that of Israel, are usually characterized by scarce resources and the necessity to make rapid policy decisions. Knowledge transfer and exchange (KTE) has emerged as a paradigm to start bridging the “know-do” gap. The purpose of this study was to explore the views of health system policymakers and senior executives involved in the policy development process in Israel regarding the role of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“… 28 Most participants in the study conducted by Ellen et al also believed that the available research evidences are not usually relevant to the policy issues. 16 Some of the participants in the study of El-Jardali et al stated that the available research evidences do not provide sufficient information on the effects and costs of policy options. 9 Moreover, most participants in the study of Hyder et al pointed out that the researchers in developing countries are not capable enough to conduct health-policy-related research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 28 Most participants in the study conducted by Ellen et al also believed that the available research evidences are not usually relevant to the policy issues. 16 Some of the participants in the study of El-Jardali et al stated that the available research evidences do not provide sufficient information on the effects and costs of policy options. 9 Moreover, most participants in the study of Hyder et al pointed out that the researchers in developing countries are not capable enough to conduct health-policy-related research.…”
Section: Discussionmentioning
confidence: 99%
“…They also believed that a specific research is better than general one. 16 The participants of the study of El-Jardali et al study emphasized the necessity of training the policy-makers on the methods of acquisition, assessment, and adaptation of policy options. 9 One of the tools in SUPPORT deals with the assessment of local applicability of the systematic review findings in different settings and poses various questions about the possibility of their use in the local context such as the similarities of the findings in different contexts, the effect of on-the-ground realities and constraints on the feasibility of interventions, the effect of different arrangements of health system on the effectiveness of interventions, and the effect of baseline conditions on the absolute effects of the interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of early users of OMB/PTV/r + DSV in MHS in 2015, SVR rates similar to clinical trials (>90%) were observed in the real-world setting, including among patients with cirrhosis and comorbidities [ 14 ]. In this respect, the experience of MHS with this model of HCV treatment delivery will continue to be evaluated in parallel to real-world HCV patient outcomes in order to monitor long-term outcomes, inform data-driven decisions, and improve knowledge transfer and exchange [ 15 ]. Currently, patients who do not meet eligibility criteria of the national basket of health services may receive DAA therapy through complementary insurance with the health plans, and while these different pathways exist the very small number of patients taking advantage of this option indicates that it is important to apply a similar model to ensure equitable access and quality of care for all patients.…”
Section: Discussionmentioning
confidence: 99%